Effect of Gender in MGA (Multi Group Analysis) on Nano Influencer Relationship on Buying Decisions - Ardiansyah, Tedy; Nurjanah, Nurjanah; Purwaningsih, Dewi; Hasan, Rahmawati (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
The problem currently facing students is that in the digital age they are still not maximizing opportunities for digital entrepreneurship, so a lot of time is wasted. As an influencer is one solution to get purchasing decisions from consumers. The research method using the Multigroup Analysis (MGA) approach with the partial least squares path modeling (PLSPM) approach is an effective method for analyzing moderation in various relationships in the research model. The samples taken were students who were active as influencers. The sampling technique was carried out using purposive sampling where there were 125 respondents throughout Jabodetabek. The results of the research are that all 4 hypotheses relating to nano influencers (ni) on decision buying (kp) through sex or gender moderators, whether male or female, all have a positive and significant effect, but men have advantages for sex or gender compared to women as moderators of nano influencer (ni) on decision buying (kp) are shown by a path coefficient value of 0.713.